Sarcoidosis Vasculitis and Diffuse Lung Disease: alive and still growing - Baughman, Robert P.; Caminati, Antonella; Ravaglia, Claudia; Richeldi, Luca; Rottoli, Paola; Tomassetti, Sara; Vancheri, Carlo (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
In 2004, the journal Sarcoidosis was launched by Professor Gianfranco Rizzato. With the support of Drs. D. Geraint James, Carlo Agostini, and Gianpietro Semenzato, the journal quickly became the leading source of new information regarding sarcoidosis. When the World Association of Sarcoidosis and Other Granulomatous disease (WASOG) was formed, the journal was became its official journal. [...]